Descriptions of Chinese species of the subgenus Diestrammena (Gymnaeta) Adelung (Orthoptera: Rhaphidophoridae) - Jiao, Zhongjiu; Niu, Changying; Liu, Xianwei; Lei, Chaoliang; Bi, Wenxuan (Zootaxa, 2008)
Diestrammena (Gymnaeta) was erected by Adelung in 1902 (Adelung 1902). The type species is Gymnaeta berezowskii Adelung, 1902. Presently, the subgenus Gymnaeta includes 9 species (Eades et al., 2007). In the present paper, one new species D. (G.) caverna sp. n., the male of D.(G.) brevicauda (Karny, 1933), and the male of D.(G.) tianmushanensis (Liu & Zhang, 2001), D.(G.) borutzkyi Gorochov, 2004 are described. The specific name Gymnaeta brevicauda Karny, 1933 is resurrected. A key to the Chinese species of Diestrammena (Gymnaeta) is given. All the materials are deposited in the Shanghai Entomological Museum, Chinese Academy of Science.